2021
DOI: 10.1186/s40644-020-00373-4
|View full text |Cite
|
Sign up to set email alerts
|

Detecting recurrent prostate Cancer using multiparametric MRI, influence of PSA and Gleason grade

Abstract: Background The utility of multiparametric MRI (mpMRI) in detecting suspected local recurrence post radical prostatectomy (RP) may be associated with PSA and Gleason grade. The purpose of the study was to evaluate the likelihood of detecting locally recurrent prostate cancer utilizing mpMRI in patients with suspected recurrence following radical prostatectomy (RP) parsed by PSA and Gleason grade. Methods One hundred ninety five patients with suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…In addition, the PSA value was the risk factor found in all clinical risk factors. This result is similar to a recent report on radiomic machine learning ( 29 ). The performance of both the radiomic signature and PSA value was high and comparable in the testing group in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the PSA value was the risk factor found in all clinical risk factors. This result is similar to a recent report on radiomic machine learning ( 29 ). The performance of both the radiomic signature and PSA value was high and comparable in the testing group in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The performance of both the radiomic signature and PSA value was high and comparable in the testing group in our study. In a previous study, Calvocoressi ( 29 ) found that the older the patient, the higher risk of histological malignancy of prostate nodules. The OR and 95% CI values of prostate tissue with a worse prognosis were 2.21 (1.30~3.76) and 1.58 (0.90–2.76), respectively, for men aged over 80 and under 70 years old.…”
Section: Discussionmentioning
confidence: 95%
“…Comparing mpMRI and 11 C-choline PET/CT, Kitajima et al [18] reported 52.4% of local recurrences were correctly diagnosed by both modalities whereas 36.1% were correctly diagnosed by only mpMRI; they reported mpMRI sensitivity, specificity, and accuracy for diagnosing local recurrence were 88.5, 84.6, and 87.4%, respectively. Venkatesan et al found in a clinical setting that mpMRI is very likely to be negative if PSA is less than 0.5 ng/ml for low Gleason-grade tumors but not high-grade, whereas, for high-grade tumors, mpMRI is almost always positive if PSA is greater than 1.5 ng/ml, suggesting that between these values, mpMRI is more likely to be diagnostic; and, in the latter scenario, mpMRI is more likely to be of value for guiding biopsy [19].…”
Section: Local Recurrencementioning
confidence: 98%
“…After radical surgery, mpMRI can be used to analyze the operation situs in case of biochemical recurrence. However, the performance of the examination depends on Prostate Specific Antigen (PSA) levels and the Gleason grade of the initial neoplasia, as per the study of Venkatesan et al which reported 87.2% negative examinations in cases of PSA less than 0.5 ng/mL in lower grade tumor and 88.9% positive examinations in cases of PSA higher than 1.5 ng/mL in higher grade tumor [ 78 ]. From this observation, the diagnostic contribution of mpMRI is most relevant in intermediate combinations of PSA levels and Gleason grade tumors.…”
Section: Diffusion-weighted Prostate Imagingmentioning
confidence: 99%